Does Financial Inclusion Enhance per Capita Income in the Least Developed Countries? - António Afonso; M. Carmen Blanco-Arana (Center for Economic Studies and ifo Institute (CESifo), 2024)
Financial inclusion is a key factor for economic growth in most developing countries. This paper examines the relationship between financial inclusion and Gross Domestic Product (GDP) per capita in the Least Developed Countries (LDCs) using panel data for the period 1990-2021. The empirical evidence suggests that financial inclusion is indeed related to economic growth in the LDCs. We consider different dimensions of financial inclusion: usability (% of bank credit to bank deposits), accessibility (commercial bank branches), concentration (% of concentration of banks) and availability (depositors with commercial banks) to determine which has a greater effect on economic growth in the countries analyzed. Therefore, we assess which dimensions of financial inclusion are a better tool to improve the economic situation in the poorest countries in the world. While we conclude that all dimensions of financial inclusion have a positive effect on economic growth, in the expected direction, we find that not all dimensions affect economic growth similarly. The dimensions 'accessibility' and 'concentration' are robustly associated with economic growth, while 'usability' and 'availability' produce a significant but relatively lesser effect in the LDCs.
Keywords: O40; O47; C33; F30; 330; financial inclusion; GDP per capita; panel data; LDCs